Identifikasi kandungan serbuk simplisia Eleutherine bulbosa dan potensinya terhadap probiotik Pro-Kj secara in-vitro untuk akuakultur - Munaeni, Waode; Syazili, Aras; Disnawati, Disnawati (Universitas Batangahari Jambi, 2024)
The use of herbal medicines and probiotics in cultivation has now been widely used and proven to be able to improve growth performance and disease resistance, such as in herbal plants from forest onions (Eleutherine bulbosa). Field applications use herbal medicines and probiotics together in feed by fermentation. However, there is no information about E. bulbosa simplicia powder and its potential if fermented together with Pro-KJ probiotics, as well as the phytochemical content and other compounds of E. bulbosa simplicia powder. This research aims to determine the phytochemical content and other compounds of the herbal medicine forest onion as well as its prebiotic potential for Pro-KJ probiotics in vitro. The parameters observed in this study were qualitative phytochemical identification using the color visualization method, proximate detection using the gravimerti method, and total bacteria detection using the Total Plate Count (TPC) method. Three levels of simplicia powder doses were tested using the Pro-KJ probiotic co-culture method, namely doses of 0.625%, 1.25%, and 2.5%, as well as control or without the addition of E. bulbosa simplicia powder. The research results showed that the phytochemical screening of simplicia powder from E. bulbosa was positive for containing flavonoids, saponins, and steroids, while other compounds such as protein were 11.33%, water content was 9.59%, ash content was 4.66%, fat content was 2.51%, and crude fiber was 1.75%. The results of the joint culture of simplicia powder with pro-KJ probiotics showed that E. bulbosa simplicia powder did not inhibit the growth of pro-KJ probiotics. The best dose that can increase the growth of Pro-KJ probiotics is 1.25%. Thus, E. bulbosa simplicia powder can be used with Pro-KJ probiotics for aquaculture organisms.